Single key MITM attack and biclique cryptanalysis of full round Khudra. (August 2018) - Dey, Prakash; Rohit, Raghvendra Singh; Adhikari, Avishek
Abstract: Khudra, an efficient lightweight block cipher for FPGAs, requires at least around 45% less slices and 29% less AT product compared to round wise implementation of any of the contemporary lightweight block cipher. Though a few attacks on Khudra, mostly on meet-in-the-middle (MITM) attack, rectangle attack etc. with reduced rounds having high data complexity, are reported in the literature of cryptanalysis, none have been reported for single key attack on full round Khudra. In this paper, up to the best of our knowledge, we for the first time, present two single-key attacks on full round Khudra. In the first attack, we propose MITM attack on full round Khudra having time complexity 2 79.61 and data complexity 2. Next we find a 3-round biclique in the plaintext side which we utilize to attack full round Khudra with a reduced time complexity of 2 79.36 .